Cinema at the periphery - Vidal, Belen, 1974-; Martin-Jones, David; Iordanova, Dina (Contemporary approaches to film and television series., 2010)
From Iceland to Iran, from Singapore to Scotland, a growing intellectual and cultural wave of production is taking cinema beyond the borders of its place of origin - exploring faraway places, interacting with barely known peoples, and making new localities imaginable. In these films, previously entrenched spatial divisions no longer function as firmly fixed grid coordinates, the hierarchical position of place as 'center' is subverted, and new forms of representation become possible. In Cinema at the Periphery, editors Dina Iordanova, David Martin-Jones, and Belén Vidal assemble criticism that explores issues of the periphery, including questions of transnationality, place, space, passage, and migration. Cinema at the Periphery examines the periphery in terms of locations, practices, methods, and themes. It includes geographic case studies of small national cinemas located at the global margins, like New Zealand and Scotland, but also of filmmaking that comes from peripheral cultures, like Palestinian 'stateless' cinema, Australian Aboriginal films, and cinema from Quebec. Therefore, the volume is divided into two key areas: industries and markets on the one hand, and identities and histories on the other. Yet as a whole, the contributors illustrate that the concept of 'periphery' is not fixed but is always changing according to patterns of industry, ideology, and taste. Cinema at the Periphery highlights the inextricable interrelationship that exists between production modes and circulation channels and the emerging narratives of histories and identities they enable. In the present era of globalization, this timely examination of the periphery will interest teachers and students of film and media studies.